Reconsidering the impact of family size on labour supply: The twin-problems of the twin-birth instrument - Nils Braakmann; John Wildman (Leuphana Universität Lüneburg, Institut für Volkswirtschaftslehre, 2014)
Twin births are often used to instrument for fertility when investigating the impact of family size on labor market outcomes. In this paper we consider two econometric problems both related to the link between fertility treatments and multiple births. The first is the potential for omitted variable bias caused by the fact that fertility treatments are typically unobserved. We present estimates corrected for this bias and find it to be comparatively small. Second, we show that the effects of twin-birth induced variation in family size vary substantially with time passed since birth, which has consequences for the interpretation of estimates based on a single cross-section.
Keywords: C26; J13; J22; 330; twin birth instrument; quantity-quality-tradeoff; labor supply; fertility